Pinning properties of FeSeTe thin film through multifrequency measurements of the surface impedance. (29th September 2020) - Pompeo, N; Torokhtii, K; Alimenti, A; Sylva, G; Braccini, V; Silva, E
Abstract: We present high frequency measurements of the vortex dynamics of a FeSe x Te1 −  x ( x  = 0.5) thin film grown on a CaF2 substrate and with a critical temperature T c ≃ 18  K, performed by means of a dual frequency dielectric resonator at 16.4 GHz and 26.6 GHz. We extract and discuss various important vortex parameters related to the pinning properties of the sample, such as the characteristic frequency ν c, the pinning constant k p and the pinning barrier height U relevant for creep phenomena. We find that the vortex system is in the single-vortex regime, and that pinning attains relatively high values in terms of k p, indicating significant pinning at the high frequencies here studied. The pinning barrier energy U is quite small and exhibits a non-monotonous temperature dependence with a maximum near 12 K. This result is discussed in terms of core pinning of small portion of vortices of size ∝ ξ 3 jumping out of the pinning wells over very small distances, a process which is favoured in the high frequency, short ranged vortex oscillations here explored.